2017
DOI: 10.1007/s10803-017-3130-4
|View full text |Cite
|
Sign up to set email alerts
|

Medical Conditions in the First Years of Life Associated with Future Diagnosis of ASD in Children

Abstract: This study examines medical conditions diagnosed prior to the diagnosis of autism spectrum disorder (ASD). Using a matched case control design with 3911 ASD cases and 38,609 controls, we found that 38 out of 79 medical conditions were associated with increased ASD risk. Developmental delay, mental health, and neurology conditions had the strongest associations (ORs 2.0–23.3). Moderately strong associations were observed for nutrition, genetic, ear nose and throat, and sleep conditions (ORs 2.1–3.2). Using mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 49 publications
5
42
0
Order By: Relevance
“…The prevalence of other conditions previously associated with ASD and common physical problems were examined in our study population and yield inconsistent results. While being in line with previous prevalence studies regarding higher rates of comorbid neurological problems and immunological dysregulations (Davignon et al 2018 ; Kohane et al 2012 ; Schendel et al 2016 ; Schieve et al 2012 ), our data revealed no evidence for an increase of infectious diseases and congenital cardiovascular abnormalities in autism (Alexeeff et al 2017 ; Timonen-Soivio et al 2015 ). However, the trend that individuals with autism were prone to have congenital heart malformations (non-significant after the Bonferroni correction) might be associated with somatic pleiotropy of ASD-related genetic variants (Vorstman et al 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of other conditions previously associated with ASD and common physical problems were examined in our study population and yield inconsistent results. While being in line with previous prevalence studies regarding higher rates of comorbid neurological problems and immunological dysregulations (Davignon et al 2018 ; Kohane et al 2012 ; Schendel et al 2016 ; Schieve et al 2012 ), our data revealed no evidence for an increase of infectious diseases and congenital cardiovascular abnormalities in autism (Alexeeff et al 2017 ; Timonen-Soivio et al 2015 ). However, the trend that individuals with autism were prone to have congenital heart malformations (non-significant after the Bonferroni correction) might be associated with somatic pleiotropy of ASD-related genetic variants (Vorstman et al 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…Peripheral concentrations of cytokines and chemokines involved in the innate and adaptive immune responses vary in individuals already diagnosed with ASD compared to controls (3,4), though the prevalence of multiple disorders of the immune system (e.g., asthma, infections, allergy, autoimmune disorders) is also higher in individuals with ASD (5)(6)(7). Integrative analyses of genetic and transcriptomic data suggest that ASD and several of these commonly co-occurring conditions may be related via shared mechanisms involving innate immunity (8).…”
Section: Introductionmentioning
confidence: 99%
“…Lingren et al [] examined COC diagnoses in electronic health records from three clinical sites and used cluster analysis to identify subtypes of ASD in a pediatric population. Clustering based on medical conditions diagnosed prior to ASD diagnosis, including COCs, was also performed by Alexeeff et al [] to predict future ASD diagnosis risk from electronic health records and medical claims of health plan members aged 2–12 years old. There is thus great potential for using recorded healthcare data to study COC diagnosis patterns and characterize possible subtypes of ASD from these diagnoses.…”
Section: Introductionmentioning
confidence: 99%